Effect of different waterlogging periods on biochemistry, growth, and chlorophyll a fluorescence of Arachis hypogaea L. - Sharma, Shubhangani; Bhatt, Upma; Sharma, Jyotshana; Darkalt, Ahmad; Mojski, Jacek; Soni, Vineet (Frontiers in Plant Science, 2022)
Peanut is among the main oil crops in India with huge economic importance. The unpredictable rainy season during the growing time of peanuts causes waterlogging in peanut fields. Waterlogging triggers major environmental limitations that negatively affect the growth, physiology, and development of peanuts. Thus, the export and production of peanuts are severely affected by waterlogging. Therefore, the understanding of metabolic mechanisms under waterlogging is important to future water-stress tolerance breeding in peanuts. This study aimed to evaluate how peanuts responded to various waterlogging conditions in terms of their development, metabolic processes, and chlorophyll fluorescence characteristics. The evaluations were carried out at different stages of peanut variety DH-86 treated with waterlogging. The peanut plants were subjected to different waterlogging periods of 20, 40, 60, 80, and 100 days. The growth parameters including total dry mass, total leaf area, and total leaves number were calculated in all treatments. The phenomenological and specific energy fluxes and maximum photosystem II efficiency (FV/Fm) were also determined. The measurements were done statistically using PCA, G-Means clustering, and correlation analysis to explore the interaction between different physiological parameters. The waterlogging for 100 days caused a significant reduction in the total number of leaves, dry mass, and total leaf area. The most sensitive parameters are specific and phenomenological energy fluxes and Fv/Fm, which notably decreased as waterlogging duration increased. The results indicated the growth and physiological performance of the peanut cv. DH-86 was affected significantly due to waterlogging and the interaction between all these parameters in waterlogging. This research focused on how peanuts respond to waterlogging stress and provides the basis for future plant breeding efforts to improve peanut waterlogging tolerance, especially in rainy regions. This will improve the sustainability of the entire peanut industry.